Overproduction of ABA in rootstocks alleviates salinity stress in tomato shoots - Martínez-Andújar, Cristina; Martínez-Pérez, Ascensión; Albacete, Alfonso; Martínez-Melgarejo, Purificación A.; Dodd, Ian C.; Thompson, Andrew J.; Mohareb, Fady R.; Estelles-Lopez, Lucia; Kevei, Zoltan; Ferrández-Ayela, Almudena; Pérez‑Pérez, José Manuel; Gifford, Miriam L.; et al. (Wiley, 2021)
To determine whether root-supplied ABA alleviates saline stress, tomato (Solanum lycopersicum L. cv. Sugar Drop) was grafted onto two independent lines (NCED OE) overexpressing the SlNCED1 gene (9-cis-epoxycarotenoid dioxygenase) and wild type rootstocks. After 200 days of saline irrigation (EC = 3.5 dS m−1), plants with NCED OE rootstocks had 30% higher fruit yield, but decreased root biomass and lateral root development. Although NCED OE rootstocks upregulated ABA-signalling (AREB, ATHB12), ethylene-related (ACCs, ERFs), aquaporin (PIPs) and stress-related (TAS14, KIN, LEA) genes, downregulation of PYL ABA receptors and signalling components (WRKYs), ethylene synthesis (ACOs) and auxin-responsive factors occurred. Elevated SlNCED1 expression enhanced ABA levels in reproductive tissue while ABA catabolites accumulated in leaf and xylem sap suggesting homeostatic mechanisms. NCED OE also reduced xylem cytokinin transport to the shoot and stimulated foliar 2-isopentenyl adenine (iP) accumulation and phloem transport. Moreover, increased xylem GA3 levels in growing fruit trusses were associated with enhanced reproductive growth. Improved photosynthesis without changes in stomatal conductance was consistent with reduced stress sensitivity and hormone-mediated alteration of leaf growth and mesophyll structure. Combined with increases in leaf nutrients and flavonoids, systemic changes in hormone balance could explain enhanced vigour, reproductive growth and yield under saline stress.
Keywords: 9-cis-epoxycarotenoid dioxygenase; abscisic acid; plant hormones; root gene expression; rootstocks; salt stress; tomato (Solanum lycopersicum)